Guaranteed stable PID controller tuning rules for First-Order Dead-time Unstable Processes - Nandong, Jobrun (2015)
An open-loop unstable process with dead-time is commonly encountered in process industry. A PID controller design that can provide both closed-loop stability and good performance-robustness tradeoffs is difficult to accomplish for the unstable process compared with that for the stable one. In this paper, a set of PID tuning rules for the First-Order Dead-time Unstable Process (FODUP) is proposed. These rules ensure the attainment of simultaneous closed-loop stability and good performance-robustness tradeoffs. Some correlations are also presented to facilitate with the setpoint pre-filter design for suppressing excessively high overshoot caused by a step change in the setpoint. Numerical studies confirm the effectiveness of the proposed rules. © 2015 IEEE.